2011
DOI: 10.1007/s10728-011-0189-5
|View full text |Cite
|
Sign up to set email alerts
|

Goals of Clinical Ethics Support: Perceptions of Dutch Healthcare Institutions

Abstract: In previous literature, ethicists mention several goals of Clinical Ethics Support (CES). It is unknown what key persons in healthcare institutions see as main–—and sub-goals of CES. This article presents the goals of CES as perceived by board members and members of ethics support staff. This is part of a Dutch national research using a mixed methods design with questionnaires, focus groups and interviews. Quantitative and qualitative data were analyzed and combined in an iterative process. Four main clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
4
25
0
2
Order By: Relevance
“…In the following section highlighted results are discussed and compared with existing literature on CESS outcomes. A study by Dauwerse et al (2013) shows that participants thought that CESS goals included encouraging a moral climate, as well as developing professionalism and good care [28], which is comparable with themes presented in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In the following section highlighted results are discussed and compared with existing literature on CESS outcomes. A study by Dauwerse et al (2013) shows that participants thought that CESS goals included encouraging a moral climate, as well as developing professionalism and good care [28], which is comparable with themes presented in our study.…”
Section: Discussionsupporting
confidence: 86%
“…MCD as a dialogical and pragmatist way of ethics support is well known in the Netherlands (Dauwerse et al 2013). The method consists of a methodical, joint philosophical inquiry into a concretely experienced moral question related to a concrete situation by a-preferably multidisciplinary-group of health care professionals.…”
mentioning
confidence: 99%
“…Edwards, McClement, and Read (2013) showed that healthcare professionals can help each other to address and act upon the issues at stake by communicating the ethically difficult situations with co-workers. Other studies stress the importance for healthcare professionals to systematically reflect on moral issues in organized forms so as to make the various perspectives and interpretations transparent (Pedersen, Akre, & Førde, 2009), to promote good care in concordance with patients' needs (Dauwerse, Abma, Molewijk, & Widdershoven, 2013), and to further prevent moral distress among the professionals (Silén, Svantesson, Kjellström, Sidenvall, & Christensson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of clinical ethics support (CES) have been developed to promote the possibilities for healthcare professionals to communicate and handle ethical issues (Rasoal, Skovdahl, Gifford, & Kihlgren, 2017), such as moral case deliberation (MCD) (van der Dam, Abma, Molewijk, Kardol, & Schols, 2011), ethics consultations (Fox, Myers, & Pearlman, 2007), clinical ethics committees (Pedersen et al, 2009 a), and ethical rounds (Svantesson, Anderzen-Carlsson, Thorsen, Kallenberg, & Ahlström, 2008). The various forms of CES aim to raise awareness of ethical issues (Dauwerse et al, 2013), broaden perspectives (Gracia, 2003), and reflections on how to deal with moral issues (Hermsen & van der Donk, 2009). The CES intervention described in this study was inspired by Habermas' theory of communicative action.…”
Section: Introductionmentioning
confidence: 99%